Climate-Smart Villages: A community approach to sustainable agricultural development - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Climate-Smart Villages are sites where researchers, farmers’ cooperatives, government ofﬁ cials and private sector partners come together to identify the most appropriate climate-smart interventions in agriculture based on its agro-ecological, climate risk proﬁ le and socio-economic conditions. These interventions include water smart practices (rainwater harvesting, laser levelling), weather smart activities (ICT-based agromet services, index-based insurance), nitrogen and carbon smart practices (precision fertilizers, catch-cropping), energy smart (zero tillage, residue management) and knowledge smart activities (farmer-farmer learning, seed banks and cooperatives). These interventions work together increase an agriculture community’s resilience to climatic stresses.